Perancangan Sistem Penyewaan Motor Pada PT. Caraka Trans Jakarta - Yogasetya Suhanda; Septiana Ningtyas; D Dedi (STIKOM Tunas Bangsa Pematangsiantar, 2026)
The development of information technology has encouraged companies to implement computerized systems to improve service quality. PT. Caraka Trans Jakarta still rents motorbikes by phone or by having the renter come directly to the location, making it difficult to obtain information about motorbike availability quickly. Furthermore, unintegrated recording has the potential to lead to manipulation of rental and financial data. This study used qualitative methods with observation and interview techniques, while a SWOT analysis was used as the basis for system design. The results produced a web-based motorbike rental information system using the Laravel framework and a MySQL database that supports the rental, payment, return, and data management processes by the admin. Based on a feasibility analysis of technological, operational, and legal aspects, the system was declared feasible to implement. The implementation of the system can speed up the rental process, simplify transactions, reduce the potential for data manipulation, and improve service efficiency for renters..